Proximate composition, B-vitamin content and sensory properties of cookies produced from wheat–Egusi (Citrullus colocynthis) flour blends (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the proximate composition, vitamins (B1 and B2), and sensory attributes of cookies produced from wheat and egusi (Citrullus colocynthis) flour blends. Egusi seeds were dehulled, washed, oven-dried, and milled into flour, which was subsequently blended with all-purpose wheat flour in varying proportions (100:0, 95:5, 90:10, 85:15, and 80:20) to produce cookies. The formulated cookies were analyzed for proximate composition and micronutrient content using standard methods. Sensory evaluation was conducted using a structured nine-point hedonic scale, with the control sample (W100E0) included for comparison. The ash content increased from 1.33% to 1.81%, and protein (17.63 - 19.99%), fat (14.10 - 24.00%), and carbohydrate rose from 35.59% to 54.52%, compared to the control (W100E0) values, which were 1.25%, 12.36%, 21.41%, and 43.04%, respectively. A slight reduction was observed in moisture content (10.46 - 16.30%) and fiber content (1.28 - 1.91%) relative to the control. Sensory evaluation revealed that all the cookie samples were generally acceptable to the panelists, with the 100:0 (W100E0) and 90:10 (W90E10) formulations receiving the highest preference scores. The findings suggest that the inclusion of Egusi flour in cookie production enhances nutritional quality while maintaining good sensory attributes, making it a viable ingredient for cookie fortification.
Keywords: Cookie; Micronutrient profiling; Protein enrichment; Seed flour composites